Growth rate of the crab Dissodactylus crinitichelis Moreira, 1901 (Crustacea : Decapoda : Pinnotheroidea) under laboratory conditions - Fumis, Patricia B.; Fransozo, Adilson; Bertini, Giovana; Braga, Adriane A.; Pie, Marcio R. (Biol Soc Washington, 2006)
The goal of the present study was to investigate the growth rate of the crab Dissodactylus crinitiehelis, its molt increments, and the duration of the intermolt intervals under laboratory conditions, focusing on differences between sexes and between juvenile and adult phases. Crabs were collected at Flamengo Beach, Ubatuba, São Paulo State, Brazil, by scuba divers. In the laboratory, individuals were maintained in isolation and fed nauplii of Artemia sp. daily. The sex and carapace width of exuviae and dead crabs were recorded. During the juvenile phase, mean growth was 11.8 +/- 2.7% in males and 11.2 +/- 3.6% in females, with their respective intermolt intervals 25.4 +/- 9.2 and 26.4 +/- 8.3 d (mean +/- SD). After reaching morphological sexual maturity, the intermolt intervals increased to 33.4 10.1 d in males and 32.7 +/- 10.4 d in females, and the growth rates of both sexes slowed to 6.4 +/- 1.9% in males and 5.7 +/- 1.6% in females. There was a significant decrease in molt increment and an increase in intermolt intervals associated with the maturation from juveniles to adults, evidencing differential energy allocation during the last phase of ontogeny.